Glass powder, conductive paste, and method for producing laminated ceramic capacitor
By using a conductive paste made of a specific composition of glass powder, the lack of performance of the external electrode of the laminated ceramic capacitor in terms of high capacity and temperature characteristics is solved, and sufficient adhesion to the laminated chip and efficient capacitor performance are achieved.
Patent Information
- Application Number
- CN202411858905.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-12-21
- Filing Date
- 2024-12-17
- Publication Date
- 2025-06-24
AI Technical Summary
The external electrodes of existing stacked ceramic capacitors have insufficient performance in terms of high capacity and temperature characteristics, especially the requirements for the bonding performance of a wide range of materials.
A conductive paste containing a glass powder of a specific composition ratio is provided, which contains SiO2, B2O3, ZnO, Al2O3 and CaO in terms of mass ratio based on oxide conversion, and does not contain BaO. This conductive paste is used to calcinate to form an external electrode to ensure sufficient adhesion to the laminated chip.
By using this conductive paste, the bonding performance between the external electrode of the laminated ceramic capacitor and the laminated chip can be significantly improved, and the high capacity and temperature characteristics requirements can be met.
Smart Images

Figure CN120192095A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to glass powder, conductive paste, and a method for manufacturing a multilayer ceramic capacitor. Background Art
[0002] In recent years, multilayer ceramic electronic components such as multilayer ceramic capacitors (MLCCs), multilayer inductors, and multilayer piezoelectric elements (multilayer varistors) have been used in a wide range of fields. For example, an MLCC has a stacked chip in which dielectric layers containing a ceramic material and internal electrode layers containing a conductive material are alternately stacked. Further, external electrodes are formed on the outside (e.g., side surface) of the stacked chip and are connected to the plurality of internal electrode layers, respectively. The external electrode is formed, for example, by baking a conductive paste containing conductive particles and glass powder.
[0003] Regarding the external electrode, adhesive properties to the stacked chip are required from the viewpoint of conduction reliability. In this regard, Patent Document 1 discloses a glassy glass frit in which the ratio of each element constituting the glass is a specified ratio in terms of oxide conversion, and a conductive composition for a ceramic capacitor terminal electrode dispersed in an organic carrier.
[0004] Prior Art Documents
[0005] Patent Documents
[0006] Patent Document 1: Japanese Patent Publication No. Hei 8-17140 Summary of the Invention
[0007] Problems to be Solved by the Invention
[0008] However, in recent years, with the increasing demand for multilayer ceramic capacitors, various performances such as high capacitance and temperature characteristics have been required. Therefore, the stacked chips constituting the multilayer ceramic capacitors also vary depending on the main components. Therefore, for the conductive paste for external electrode use, adhesive properties to a wide range of materials are required.
[0009] The technology disclosed herein has been completed in view of this, and an object thereof is to provide a general-purpose glass powder that can obtain sufficient adhesive properties to the stacked chips constituting various multilayer ceramic capacitors. Further, as another aspect, an object thereof is to provide a conductive paste containing the glass powder and a method for manufacturing a multilayer ceramic capacitor using the conductive paste.
[0010] Means for Solving the Problems
[0011] The glass powder disclosed herein is glass powder for a conductive paste, and the glass powder contains the following composition in terms of mass ratio in terms of oxide conversion:
[0012] SiO2: 6 wt% to 18 wt%; B2O3: 18 wt% to 30 wt%; ZnO: 26 wt% to 47 wt%; Al2O3: 2 wt% to 17 wt%; CaO: 10 wt% to 25 wt%, and substantially free of BaO.
[0013] In the above glass powder, the mass ratio of the glass powder is controlled as described above in terms of oxides. Thus, it was confirmed that the glass powder melted and sufficient adhesiveness between the external electrode and the stacked chip was obtained when forming the external electrode. In addition, according to the in-depth research by the inventors et al., when BaO is contained in the glass powder, the adhesion performance to the stacked chip is reduced. Therefore, the above glass powder is substantially free of BaO. Thus, a reduction in the adhesion performance to the stacked chip can be suppressed.
[0014] In a preferred embodiment of the glass powder disclosed herein, the glass powder is substantially free of alkaline earth metal oxides other than CaO.
[0015] In a preferred embodiment of the glass powder disclosed herein, the softening point of the glass powder is 500 °C or higher and 650 °C or lower.
[0016] In a preferred embodiment of the glass powder disclosed herein, the median particle size D 50 of the glass powder is 1 μm or more and 3 μm or less.
[0017] In a preferred embodiment of the glass powder disclosed herein, the glass powder contains 20 wt% or more of B2O3 in terms of the mass ratio in terms of oxides.
[0018] In a preferred embodiment of the glass powder disclosed herein, the glass powder contains 10 wt% or more of Al2O3 in terms of the mass ratio in terms of oxides.
[0019] In addition, as another aspect of the technology disclosed herein, a conductive paste containing the glass powder, conductive particles, and a dispersion medium disclosed herein is provided. Thus, sufficient adhesiveness to the stacked chip can be obtained when baking the above conductive paste.
[0020] In a preferred embodiment of the conductive paste disclosed herein, the above conductive particles are Cu particles.
[0021] In a preferred embodiment of the conductive paste disclosed herein, when the entire conductive paste is set to 100 wt%, it contains 4 wt% or more and 12 wt% or less of the above glass powder.
[0022] Furthermore, as another aspect of the technology disclosed herein, a method for manufacturing a multilayer ceramic capacitor is provided. The method for manufacturing a multilayer ceramic capacitor disclosed herein is characterized by including: a stacked chip preparation step of preparing a stacked chip; a paste coating step of coating the conductive paste prepared in the paste preparation step on the surface of the stacked chip prepared in the stacked chip preparation step; and a firing step of firing the stacked chip coated with the conductive paste. Here, the glass powder contains the following composition in terms of the mass ratio in terms of oxide conversion:
[0023] SiO2: 6 wt% to 18 wt%; B2O3: 18 wt% to 30 wt%; ZnO: 26 wt% to 47 wt%; Al2O3: 2 wt% to 17 wt%; CaO: 10 wt% to 25 wt%, and substantially does not contain BaO. Thus, a multilayer ceramic capacitor with sufficient adhesion performance between the stacked chip and the external electrode can be obtained.
[0024] In a preferred embodiment of the method for manufacturing a multilayer ceramic capacitor disclosed herein, the stacked chip includes a dielectric layer mainly composed of a perovskite-type oxide.
[0025] In a preferred embodiment of the method for manufacturing a multilayer ceramic capacitor disclosed herein, as the perovskite-type oxide, (CaSr)(TiZr)O3 is included.
[0026] In a preferred embodiment of the method for manufacturing a multilayer ceramic capacitor disclosed herein, the firing step is performed at a firing temperature of 650 °C or higher and 850 °C or lower. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a schematic cross-sectional view schematically illustrating the structure of an MLCC manufactured using a conductive paste containing a glass powder of one embodiment.
[0028] Figure 2 is a photograph after a scratch test of an evaluation electrode formed using Sample 1.
[0029] Figure 3 is a photograph after a scratch test of an evaluation electrode formed using Sample 4.
[0030] Figure 4 is a photograph after a scratch test of an evaluation electrode formed using Sample 5.
[0031] Figure 5 is a photograph after a scratch test of an evaluation electrode formed using Sample 12.
[0032] DESCRIPTION OF REFERENCE NUMERALS
[0033] 1 Multi-layer Ceramic Capacitor (MLCC)
[0034] 10-layer chip
[0035] 20 dielectric layers
[0036] 30 internal electrode layers
[0037] 40 external electrodes Detailed implementation manners
[0038] Hereinafter, preferred implementation manners of the technology disclosed herein will be described. It should be noted that matters required for implementing the technology disclosed herein other than those specifically mentioned in this specification can be grasped as design matters of those skilled in the art based on the prior art in this field. The technology disclosed here can be implemented based on the content disclosed in this specification and the common general knowledge in this field. It should be noted that the expression "A to B" indicating a numerical range in this specification means "not less than A and not more than B".
[0039] [Glass powder]
[0040] The glass powder disclosed herein is used for the purpose of conductive paste. The glass powder of the present invention melts during paste firing to become a liquid glass component. Then, the liquid glass component is filled into the gaps of the sintered body of conductive particles to densify the external electrodes and has the function of imparting adhesion performance. Moreover, the glass powder disclosed herein is characterized in that it contains the following composition in terms of mass ratio in terms of oxides and substantially does not contain BaO. Hereinafter, the glass powder disclosed herein will be described.
[0041] SiO2: 6 wt% to 18 wt%;
[0042] B2O3: 18 wt% to 30 wt%;
[0043] ZnO: 26 wt% to 47 wt%;
[0044] Al2O3: 2 wt% to 17 wt%;
[0045] CaO: 10 wt% to 25 wt%.
[0046] (1) Composition of the glass powder
[0047] In this item, the specific composition of the glass powder disclosed herein will be described.
[0048] (a) Silicon oxide (SiO2)
[0049] SiO2 is one of the components that can form the glass skeleton alone (glass skeleton-forming components). As the proportion of SiO2 in the glass skeleton-forming components increases, the thermal stability of the glass powder improves. In addition, SiO2 also has the function of improving the chemical resistance of the glass powder. From this perspective, in the technology disclosed herein, the content ratio of SiO2 in the glass powder is set to 6 wt% or more. It should be noted that from the perspective of the thermal stability and chemical resistance of the glass powder, the content ratio of SiO2 is preferably 7.5 wt% or more, more preferably 10 wt% or more. On the other hand, from the perspective that if the content ratio increases, the viscosity during melting becomes too high, in the technology disclosed herein, the content ratio of SiO2 in the glass powder is set to 18 wt% or less. It should be noted that from this perspective, the content ratio of SiO2 in the glass powder is preferably 16.5 wt% or less, more preferably 12 wt% or less.
[0050] (b) Boron oxide (B2O3)
[0051] B2O3 is one of the glass skeleton-forming components. That is, the glass powder disclosed herein is a borosilicate glass that contains SiO2 and B2O3 in the glass skeleton. In this borosilicate glass, as the proportion of B2O3 in the glass skeleton increases, the fluidity of the molten glass composition tends to improve, bringing sufficient bonding performance. From this perspective, in the technology disclosed herein, the content ratio of B2O3 in the glass powder is set to 18 wt% or more. It should be noted that from the perspective of further improving the fluidity of the glass composition, the content ratio of B2O3 is preferably 20 wt% or more, more preferably 23 wt% or more, and particularly preferably 24 wt% or more. On the other hand, if the proportion of B2O3 is too high, the fluidity of the glass composition is too high, and thus the glass may sometimes ooze out to the electrode surface. As a result, it may cover the metal component and hinder conduction. Therefore, in the technology disclosed herein, the upper limit of the content ratio of B2O3 is set to 30 wt% or less. It should be noted that from the perspective of conduction reliability, the content ratio of B2O3 in the glass powder is preferably 27 wt% or less, preferably 25 wt% or less.
[0052] (c) Zinc oxide (ZnO)
[0053] ZnO is a component capable of modifying the glass skeleton (glass skeleton modifying component). This ZnO has the functions of improving the fusibility of the glass and adjusting the viscosity of the glass composition during roasting, and improving water resistance, thermal shock resistance, etc. In the technology disclosed herein, from the viewpoint of improving water resistance, thermal shock resistance, etc., the content ratio of ZnO in the glass powder is set to 26 wt% or more. It should be noted that from the viewpoint of improving water resistance, thermal shock resistance, etc., the content ratio of ZnO in the glass powder is preferably 32 wt% or more, more preferably 35 wt% or more, and particularly preferably 40 wt% or more. Thereby, an external electrode with more excellent durability can be formed. On the other hand, from the viewpoint of suppressing the decrease in adhesion performance caused by the excessive increase in the fluidity of the glass composition, the upper limit of the content ratio of ZnO is set to 47 wt% or less. It should be noted that from the viewpoint of suppressing the decrease in adhesion performance, the content ratio of ZnO in the glass powder is preferably 45 wt% or less, more preferably 43 wt% or less, and particularly preferably 41 wt% or less.
[0054] (d) Aluminum oxide (Al2O3)
[0055] Al2O3 has the function of stabilizing the glass skeleton and contributes to the chemical resistance and adhesion performance of the external electrode after roasting. In the technology disclosed herein, from the viewpoint of imparting general adhesion performance to the external electrode after roasting, the content ratio of Al2O3 in the glass powder is set to 2 wt% or more. It should be noted that from the viewpoint of forming an external electrode with more general adhesion performance, the content ratio of Al2O3 in the glass powder is preferably 2 wt% or more, more preferably 8 wt% or more, and particularly preferably 10 wt% or more. On the other hand, if the content ratio of Al2O3 in the glass powder increases, there is a tendency for the fluidity of the glass composition during roasting to decrease and the adhesion performance to decrease. Therefore, from the viewpoint of generating sufficient fluidity of the glass composition in the initial stage of roasting, the upper limit of the content ratio of Al2O3 is set to 17 wt% or less. It should be noted that from the viewpoint of better improving the fluidity of the glass composition in the initial stage of roasting, the content ratio of Al2O3 is preferably 15 wt% or less, more preferably 14 wt% or less, and particularly preferably 12 wt% or less.
[0056] (e) Calcium oxide (CaO)
[0057] CaO is a component for modifying the glass skeleton and has the function of reducing the viscosity of the molten glass component. That is, when the glass powder containing CaO is calcined, a glass component with high fluidity that can easily diffuse to the entire external electrode is generated. Thereby, the densification of the external electrode after calcination can be greatly improved, which contributes to the sufficient adhesive property of the glass powder. In addition, in addition to the above functions, CaO also has the functions of improving chemical resistance and abrasion resistance. In the technology disclosed herein, the content ratio of CaO in the glass powder is preferably 10 wt% or more, more preferably 11 wt% or more, and particularly preferably 15 wt% or more. On the other hand, if the content ratio of CaO in the glass powder increases, there is a tendency for the adhesive property to decrease due to the excessive fluidity of the glass component. It should be noted that from the viewpoint of more appropriately suppressing the decrease in the adhesive property, the content ratio of CaO is preferably 25 wt% or less, more preferably 24 wt% or less, and particularly preferably 20 wt% or less.
[0058] (f) Barium oxide (BaO)
[0059] The glass powder disclosed herein is characterized in that it substantially does not contain barium oxide (BaO). Glass powder containing a large amount of BaO has a tendency for the coefficient of thermal expansion to increase, and thus the adhesive force may decrease. Therefore, the glass powder of the present disclosure substantially does not contain barium oxide (BaO). It should be noted that "substantially does not contain BaO" in this specification means that BaO is not intentionally added. Therefore, it can be interpreted that the situation where BaO is contained in trace amounts due to raw materials, manufacturing processes, etc. is included in the concept of "substantially does not contain BaO" in this specification. For example, when the content of BaO in the glass powder is 0.01 wt% or less (preferably 0.005 wt% or less, more preferably 0.001 wt% or less, further preferably 0.0005 wt% or less, and particularly preferably 0.0001 wt% or less), it can be said that "substantially does not contain BaO".
[0060] (g) Alkaline earth metal oxide
[0061] Although alkaline earth metal oxides other than calcium oxide (CaO) have a smaller effect compared to barium oxide, they may cause a decrease in the adhesion force to the glass powder. Therefore, in some preferred embodiments, the glass powder disclosed herein preferably substantially does not contain alkaline earth metal oxides other than calcium oxide. It should be noted that as the "alkaline earth metal oxides other than calcium oxide" in this specification, magnesium oxide (MgO) and strontium oxide (SrO) can be cited. It should be noted that the "substantially does not contain alkaline earth metal oxides other than calcium oxide" in this specification means that alkaline earth metal oxides other than calcium oxide are not intentionally added. Therefore, it can be interpreted that the case where the alkaline earth metal oxides other than calcium oxide are contained in trace amounts due to raw materials, manufacturing processes, etc. is included in the concept of "substantially does not contain alkaline earth metal oxides other than calcium oxide" in this specification. For example, when the content of alkaline earth metal oxides (except calcium oxide) in the glass powder is 0.1 wt% or less (preferably 0.05 wt% or less, more preferably 0.01 wt% or less, further preferably 0.005 wt% or less, particularly preferably 0.001 wt% or less), it can be called "substantially does not contain alkaline earth metal oxides other than calcium oxide".
[0062] (h) Other components
[0063] It should be noted that the above description does not intend to limit the composition of the glass powder disclosed herein to the above components. In the glass powder disclosed herein, as glass framework components other than SiO2 and B2O3, P2O5, Bi2O3, etc. can be included. In addition, as glass framework modifying components, components other than BaO can also be included, such as Li2O, Na2O, K2O, TiO2, MnO, FeO, Fe2O3, Fe3O4, SnO, SnO2, V2O5, ZrO2, Nb2O5, CuO, Cu2O, La2O3, CeO2, etc. The disclosed technology herein is not limited, and the total content ratio of these metal oxides is preferably 10 wt% or less, more preferably 7 wt% or less, further preferably 5 wt% or less, particularly preferably 3 wt% or less.
[0064] (2) Shape, etc. of the glass powder
[0065] Next, the content related to the shape, etc. of the glass powder will be described.
[0066] (a) Median particle size
[0067] Without limiting the technology disclosed herein, the median particle size D of the glass powder 50 is preferably 10 μm or less, more preferably 7 μm or less, further preferably 5 μm or less, particularly preferably 3 μm or less. As the median particle size D of the glass powder 50becomes smaller, and the glass powder becomes easily fusible during the baking of the paste, so there is a tendency to fully exhibit the adhesive property. On the other hand, when the median particle size D of the glass powder 50 is too small, the inorganic particles (conductive particles, glass powder) in the paste aggregate with each other, and the viscosity of the paste tends to increase. From this viewpoint, the median particle size D of the glass powder 50 is preferably 0.1 μm or more, more preferably 0.5 μm or more, still more preferably 0.7 μm or more, and particularly preferably 1 μm or more. It should be noted that, considering the adhesive property of the external electrode after baking, the median particle size of the glass powder is preferably smaller than that of the conductive particles. Thus, the fine glass powder is disposed in the gaps between the coarse conductive particles, so that the glass component is easily filled in the gaps of the sintered body of the conductive particles during baking.
[0068] (b) Aspect ratio
[0069] Next, the shape of the glass powder is not particularly limited. The glass powder may be spherical or non-spherical (e.g., rugby ball shape, columnar, needle-like, etc.). It should be noted that, from the viewpoint of suppressing the increase in the viscosity of the paste, the glass powder is preferably spherical or substantially spherical. For example, the average aspect ratio of the glass powder is typically 1 to 2, and preferably 1 to 1.5.
[0070] (c) Softening point
[0071] In addition, the softening point of the glass powder is preferably 650 °C or lower, more preferably 630 °C or lower, still more preferably 610 °C or lower, and particularly preferably 600 °C or lower. Thus, even during low-temperature baking, a glass component having appropriate fluidity is generated, so that it can contribute to the adhesive property of the external electrode after baking. On the other hand, from the viewpoint of suppressing the decrease in the adhesive property due to the excessive fluidity of the glass component, the softening point of the glass powder is preferably 500 °C or higher, more preferably 520 °C or higher, and particularly preferably 540 °C or higher. It should be noted that the "softening point" in this specification is the temperature at which the glass starts to soften and deform due to its own weight. Typically, the softening point can be set as the "temperature at which the glass viscosity reaches about 10 7.6 dPa·s" measured according to JIS R 3103-1 (2001).
[0072] [Conductive paste]
[0073] As another aspect of the technology disclosed herein, a conductive paste is provided. The conductive paste of the present disclosure contains at least conductive particles, the glass powder having the above-described configuration, and a dispersion medium. Hereinafter, each component of the conductive paste disclosed herein will be described.
[0074] 1. Conductive particles
[0075] The conductive particles are materials that are the main components of the fired external electrodes. The conductive particles can be metal particles having the desired conductivity without particular limitation. As an example of the conductive particles, elemental metals such as nickel (Ni), palladium (Pd), platinum (Pt), gold (Au), silver (Ag), copper (Cu), ruthenium (Ru), rhodium (Rh), osmium (Os), iridium (Ir), aluminum (Al), tungsten (W), etc., and alloys containing these metals can be cited. In addition, any one of the above metal materials can be used alone for the conductive particles, or two or more thereof can be used in combination. It should be noted that among the above conductive particles, Cu particles are inexpensive and have appropriate conductivity, so they are particularly suitable as the main components of the external electrodes.
[0076] In addition, the content of the conductive particles in the conductive paste is not particularly limited and can be appropriately adjusted as needed. It should be noted that from the viewpoint of improving the conductivity of the fired external electrodes, the content of the conductive particles is preferably 60 wt% or more, more preferably 65 wt% or more, and further preferably 70 wt% or more. On the other hand, from the viewpoint of ensuring that the content of the glass powder is a certain amount or more and sufficiently obtaining the adhesiveness of the external electrodes, the upper limit of the content of the conductive particles is preferably 90 wt% or less, more preferably 85 wt% or less, and further preferably 80 wt% or less. It should be noted that unless otherwise specified, the "content" in this specification refers to the mass ratio when the total mass of the conductive paste is set to 100 wt%.
[0077] In addition, the particle size of the conductive particles is not particularly limited, and the particle sizes that can be adopted in the field of conductive pastes can be applied without particular limitation. For example, the median particle size of the conductive particles can be 0.1 μm or more, can be 0.25 μm or more, can be 0.5 μm or more, or can be 1 μm or more. In addition, the median particle size of the conductive particles can be 50 μm or less, can be 25 μm or less, or can be 10 μm or less. It should be noted that the "median particle size" in this specification is the particle size (volume sphere equivalent diameter) corresponding to the cumulative value of 50% from the smaller particle size side in the particle size distribution based on the volume standard of the laser diffraction scattering method.
[0078] In addition, the shape of the conductive particles is not particularly limited. For example, the shape of the conductive particles can be spherical or non-spherical. The non-spherical shape can be, for example, plate-like, flaky, lamellar, irregular, etc. From the viewpoint of easily increasing the packing density of the conductive particles, as the spherical conductive particles, for example, conductive particles having an aspect ratio of 1.2 or less, preferably 1.15 or less, and for example 1.1 or less can be preferably used. In addition, from the viewpoint of easily increasing the contact area of the conductive particles, as the non-spherical conductive particles, for example, conductive particles having an aspect ratio exceeding 1.2, preferably 1.3 or more, 1.5 or more, for example 1.7 or more, and further preferably 2 or more can be used. From the viewpoint of synergistically achieving the above effects, the conductive particles can be a mixture of spherical conductive particles and non-spherical conductive particles. Thus, when the solvent is removed from the paste by drying, the plurality of conductive particles come into appropriate contact, and the conductivity of the conductive film can be improved. It should be noted that the "average aspect ratio" in this specification is calculated based on electron microscope observation. Specifically, the aspect ratio is the ratio (b / a) of the length (b) of the long side to the length (a) of the short side when a rectangle circumscribing the particle is drawn in an electron microscope photograph. Moreover, the average aspect ratio is the arithmetic average of the aspect ratios obtained for 100 particles.
[0079] The content of the glass powder in the conductive paste is preferably adjusted appropriately as needed. It should be noted that as the content of the glass powder increases, the bonding performance of the external electrode after firing can be appropriately obtained. From this viewpoint, when the total mass of the conductive paste is set to 100 wt%, the content of the glass powder is preferably 4 wt% or more, more preferably 6 wt% or more, and further preferably 7.5 wt% or more. On the other hand, considering suppressing the decrease in bonding performance caused by glass floating, the upper limit of the content of the glass powder is preferably 12 wt% or less, more preferably 10 wt% or less.
[0080] 3. Dispersing medium
[0081] The dispersing medium is a liquid medium that disperses the above-mentioned powder materials (conductive particles, glass powder, etc.). The detailed composition of this dispersing medium is not particularly limited, and conventionally known dispersing media that can be used for preparing conductive paste can be used. In addition, since the dispersing medium is a component that is supposed to disappear through drying and firing, it preferably has a boiling point of about 150 °C or higher and about 300 °C or lower (for example, 170 °C or higher and 270 °C or lower).
[0082] It should be noted that as an example of the dispersion medium, an organic dispersion medium (non-aqueous dispersion medium) can be cited. As an example of such an organic dispersion medium, alcohol solvents such as methanol, sclareol, citronellol, phytol, geranyl linalool, TEXANOL, benzyl alcohol, phenoxyethanol, 1-phenoxy-2-propanol, terpineol, dihydroterpineol, isoborneol, butyl carbitol, and diethylene glycol can be cited; ester solvents such as terpineol acetate, dihydroterpineol acetate, isobornyl acetate, carbitol acetate, and diethylene glycol monobutyl ether acetate; and mineral spirits, etc. Among them, alcohol solvents (such as dihydroterpineol) can be preferably used.
[0083] It should be noted that the content ratio of the dispersion medium is preferably adjusted appropriately in consideration of the workability when coating the conductive paste. It should be noted that the workability during the coating of the paste can vary depending on the coating method, and therefore the content ratio of the dispersion medium is not limited to a specific value. As an example, when screen printing is used as the coating method, the content of the dispersion medium can be adjusted within the range of 5 wt% to 20 wt% (preferably 10 wt% to 15 wt%).
[0084] 4. Other Additives
[0085] It should be noted that the conductive paste disclosed herein can be used without particular limitation as long as it does not significantly impair the effects (adhesive properties) of the technology disclosed herein. For example, the conductive paste can contain binders, dispersants, thickeners, plasticizers, pH regulators, stabilizers, leveling agents, defoamers, antioxidants, sintering aids, preservatives, colorants (pigments, dyes, etc.).
[0086] For example, a binder is an additive that helps improve the fixability when applying a paste to a stacked chip and the adhesiveness between conductive particles. Additionally, like the dispersion medium, the binder is preferably a material that disappears during firing. Therefore, the binder is preferably an organic binder (typically an organic compound with a burnout temperature of 500°C or lower). It should be noted that the specific composition of the binder in the conductive paste disclosed herein is not particularly limited, and conventionally known binders can be used without particular limitation. Examples of such binders include organic polymer compounds such as rosin-based resins, cellulose-based resins, polyvinyl alcohol-based resins, polyvinyl acetal-based resins, acrylic resins, polyurethane resins, epoxy resins, phenolic resins, polyester resins, and vinyl resins. Although it also depends on the combination with the above-mentioned dispersion medium and cannot be generalized, among these organic compounds, cellulose-based resins, polyvinyl alcohol-based resins, polyvinyl acetal-based resins, acrylic resins, etc. are suitable as binders. The binder can be any one of the above-mentioned organic compounds, or two or more thereof can be used in combination. Additionally, the binder can also be a copolymer, block copolymer, etc. formed by copolymerizing these organic compounds. It should be noted that the content of the binder is preferably adjusted appropriately so as to exhibit appropriate fixability. For example, the content of the binder is preferably 1 wt% or more, more preferably 1.5 wt% or more, further preferably 2 wt% or more, and particularly preferably 2.5 wt% or more. On the other hand, from the viewpoint of preventing the residue of the binder after firing, the content of the binder is preferably 10 wt% or less, more preferably 9 wt% or less, further preferably 8 wt% or less, and particularly preferably 7.5 wt% or less.
[0087] In addition, a dispersant is an additive that inhibits the aggregation of inorganic particles (such as conductive particles and glass powder) in the paste. Specifically, the dispersant has the function of stabilizing the solid-liquid interface between the inorganic particles and the dispersion medium and preventing the aggregation of inorganic particles. Therefore, the glass powder in the paste can be uniformly dispersed, and the adhesive properties of the glass powder can be more appropriately exhibited. It should be noted that the type of the dispersant, etc. is not particularly limited, and conventionally known dispersants can be appropriately selected according to needs. As an example of such a dispersant, an anionic dispersant can be cited. The anionic dispersant has excellent adsorption force to inorganic particles, so it can appropriately disperse inorganic particles for a long time. As such an anionic dispersant, a carboxylic acid-based dispersant can be cited. Specific examples of such a carboxylic acid-based dispersant include stearic acid, oleic acid, myristic acid, palmitic acid, linoleic acid, lauric acid, linolenic acid, etc. It should be noted that the conductive paste can also contain two or more types of dispersants. The content of this dispersant is preferably adjusted within the range of 0.05 wt% to 5 wt% (preferably 0.1 wt% to 1 wt%, more preferably 0.1 wt% to 0.5 wt%).
[0088] [Use of Conductive Paste]
[0089] As described above, the conductive paste disclosed herein has been explained. The conductive paste having the above configuration is used for manufacturing multilayer ceramic electronic components typified by multilayer ceramic capacitors (MLCCs), and is suitable as an external electrode paste for forming external electrodes of the multilayer ceramic electronic components.
[0090] [Multilayer Ceramic Capacitor (MLCC)]
[0091] Hereinafter, as an example of the use of the conductive paste disclosed herein, a multilayer ceramic capacitor (MLCC) will be explained. Figure 1 is a cross-sectional schematic diagram schematically showing the structure of the MLCC. As Figure 1 shown, the multilayer ceramic capacitor (MLCC) 1 typically includes a multilayer chip 10 and external electrodes 40 formed on a pair of opposing end faces of the multilayer chip 10.
[0092] The multilayer chip 10 has a plurality of internal electrode layers 30 laminated via a dielectric layer 20. In an actual MLCC, the bonding boundaries between the dielectric layers 20 are integrated to an extent that cannot be visually recognized. The multilayer chip 10 is formed by applying a conductive paste, which is a precursor material of the internal electrode layer 30, to the surface of a ceramic green sheet, which is a precursor material of the dielectric layer 20, and then drying / calcining them simultaneously. Here, a part of the internal electrode layer 30 is exposed at the end faces of the multilayer chip 10 (at the Figure 1 left and right ends in
[0093] The dielectric layer 20 is typically composed of a laminated sintered body (ceramic substrate) of ceramic green sheets containing a ceramic dielectric. The dielectric layer 20 can be appropriately used singly or in combination of two or more from various ceramic dielectrics in conventionally known MLCCs according to the use and the like. Here, in several preferred embodiments, a dielectric layer 20 containing a perovskite-type oxide as a main component can be preferably employed. It should be noted that the "perovskite-type oxide" in this specification has a composition represented by the general formula ABO3. Here, A in the formula represents an element occupying the A site of the perovskite crystal structure, and B in the formula represents an element occupying the B site of the perovskite crystal structure. In addition, in this specification, the main component means the component having the largest content ratio in the entire dielectric layer 20, and typically, the main component accounts for 50 mass% or more, preferably 70 mass% or more, more preferably 90 mass% or more of the dielectric layer 20.
[0094] As an example of the perovskite-type oxide, BaTiO3 (barium titanate), (CaSr)(TiZr)O3 (hereinafter also referred to as "CSTZ"), SrTiO3 (strontium titanate), CaTiO3 (calcium titanate), MgTiO3 (magnesium titanate), (Bi1 / 2 Na 1 / 2 )TiO3 (sodium bismuth titanate, BNT), Pb(Zr x Ti 1-x )O3 (lead zirconate titanate, PZT), TiZnO3 (zinc titanate), Ba(Mg 1 / 3 Nb 2 / 3 )O3 (barium magnesium niobate), CaZrO3 (calcium zirconate), Ba(ZrTi)O3 (barium zirconate titanate, BZT), etc. Among them, as perovskite-type oxides, barium titanate or CSTZ can be preferably used, and CSTZ can be more preferably used.
[0095] However, the constituent components of the dielectric layer 20 are not limited to this, and components other than perovskite-type oxide components can also be used, such as TiO2 (titanium dioxide, rutile), Ti3O5 (titanium pentoxide), HfO2 (hafnium oxide), ZrO (zirconium oxide), Al2O3 (aluminum oxide), 2MgO·SiO2 (forsterite), NbO (niobium oxide), BaNd2Ti5O 14 (barium neodymium titanate), and other metal oxides such as rare earth element oxides.
[0096] It should be noted that, as is known to those skilled in the art, the perovskite crystal structure usually generates oxygen vacancies, etc. for charge compensation, etc. due to the influence of environmental temperature, atmosphere, etc., and exhibits ionic conductivity. At this time, if the amount of oxygen vacancies is set as δ, the perovskite crystal structure can be represented by the general formula ABO 3-δ It is expressed that δ typically satisfies 0 ≤ δ ≤ 1. In the technology disclosed herein, such a deviation in the composition of the oxide having a perovskite crystal structure is of course allowed. Similarly, it is known that the perovskite crystal structure is chemically solid-solution firm and can be partially replaced with ions of different valences and sizes. For example, it is also known that the ratio of the A-site element to the B-site element can deviate from 1:1. In this specification, within the scope not departing from the essence of the technology disclosed herein, the ratio of the A-site element to the B-site element is not strictly limited to 1:1. For example, it is allowed that the ratio of the A-site element to the B-site element deviates by about 1:0.95 to 1.05 (typically about 1:0.98 to 1.02).
[0097] It should be noted that Figure 1 The internal electrode layer 30 in
[0098] In the MLCC 1, a pair of external electrodes 40 are provided on the side surfaces of the stacked chip 10 including the dielectric layer 20 and the internal electrode layer 30. As an example, the internal electrode layers 30 are alternately connected to different external electrodes 40 in the stacking order. Thereby, a small-sized and high-capacity MLCC is constructed by connecting in parallel capacitor structures each including the dielectric layer 20 and a pair of internal electrode layers 30 sandwiching the dielectric layer 20. Although not shown, a metal plating layer is formed on the surface of the external electrode 40.
[0099] However, in the MLCC 1, in order to maintain the conduction reliability between the internal electrode layer 30 and the external electrode 40, adhesiveness between the external electrode 40 and the stacked chip 10 (specifically, between the external electrode 40 and the dielectric layer 20) is required. Moreover, the external electrode 40 of the MLCC 1 is formed by baking the conductive paste disclosed herein. As described above, the external electrode 40 formed using the conductive paste disclosed herein has excellent adhesiveness. Therefore, an MLCC 1 with high conduction reliability in which the external electrode 40 and the stacked chip 10 are firmly bonded (joined) can be obtained.
[0100] As an example of the use of the conductive paste containing the glass powder disclosed herein, the MLCC has been described above. It should be noted that the use of the conductive paste containing the glass powder disclosed herein is not limited to the above MLCC. As other examples of the multilayer ceramic electronic components that can use the conductive paste containing the glass powder disclosed herein, multilayer inductors, multilayer piezoelectric elements (multilayer varistors), etc. can be cited. For these electronic components, adhesiveness between the external electrode and the stacked chip is also required. For this, if the conductive paste containing the glass powder disclosed herein is used, it can contribute to sufficient adhesiveness of the external electrode. Therefore, by using the conductive paste containing the glass powder disclosed herein, multilayer inductors, multilayer varistors, etc. with high conduction reliability can be manufactured.
[0101] [Manufacturing Method of Multilayer Ceramic Capacitor]
[0102] As another aspect of the technology disclosed herein, a manufacturing method of a multilayer ceramic capacitor (MLCC) is provided. The manufacturing method at least includes a paste preparation step, a paste coating step, and a baking step. In the manufacturing method of the MLCC disclosed herein, in addition to the above steps, other steps can be included at any stage, and the manufacturing processes other than this can be the same as those in the past.
[0103] 1. Paste Preparation Step
[0104] In this step, a conductive paste containing glass powder, conductive particles, and a dispersion medium is prepared. The glass powder of the conductive paste prepared in this step is characterized in that it contains the following composition in terms of the mass ratio in terms of oxide conversion and substantially does not contain BaO. Thereby, an external electrode having general-purpose adhesive properties can be stably formed.
[0105] SiO2: 6 wt% to 18 wt%;
[0106] B2O3: 18 wt% to 30 wt%;
[0107] ZnO: 26 wt% to 47 wt%;
[0108] Al2O3: 2 wt% to 17 wt%;
[0109] CaO: 10 wt% to 25 wt%.
[0110] It should be noted that the conductive paste prepared in this step may have the above configuration except that it contains the glass powder having the above composition, which has been described above, so repeated description is omitted.
[0111] When preparing the conductive paste in this step, the conductive particles and the glass powder can be added to the dispersion medium and stirred using a conventionally well-known stirring and mixing device (such as an open mill, a magnetic stirrer, a planetary mixer, a disperser, etc.).
[0112] 2. Multilayer Chip Preparation Step
[0113] In this step, a multilayer chip 10 serving as the main body of the MLCC1 is prepared. In this step, when preparing the multilayer chip 10, for example, first, a ceramic green sheet serving as a base material is prepared. In one example, a ceramic material as a dielectric material, a binder, an organic solvent, etc. are stirred and mixed to prepare a paste for forming a dielectric layer. Then, the prepared paste is spread on a carrier sheet using a doctor blade method or the like to form a plurality of unburned ceramic green sheets. On the plurality of formed ceramic green sheets, a desired thickness (for example, submicron to micron level) is given in a predetermined pattern, and conductor films are respectively formed. This conductor film is the part that becomes the internal electrode layer after firing. After thus forming a plurality of (for example, several hundred to several thousand) unburned ceramic green sheets with conductor films, they are laminated and pressed. Thereby, an unburned multilayer chip is produced.
[0114] Next, the unburned stacked chip produced above is burned under appropriate heating conditions (for example, a temperature of about 1000 to 1300 °C). Thus, the stacked chips are burned (sintered) simultaneously to be integrally sintered. As described above, the stacked chip 10 in which a plurality of dielectric layers 20 and internal electrode layers 30 are alternately stacked can be obtained. However, this process is not limited to this method, and it can also be prepared by obtaining a pre-burned stacked chip.
[0115] The stacked chip 10 prepared in this process can be a stacked chip having a dielectric layer used in the above-mentioned conventionally known MLCC. In several embodiments, a stacked chip having a dielectric layer mainly composed of a perovskite-type oxide can be preferably employed. Since the conductive paste of the present disclosure contains the glass powder having the above composition, an external electrode 40 having sufficient adhesion to the stacked chip 10 is formed in the subsequent baking process. Therefore, even when the stacked chip 10 having a dielectric layer mainly composed of a perovskite-type oxide is employed, an MLCC 1 in which the external electrode 40 and the stacked chip 10 are bonded with sufficient strength and having excellent conduction reliability can be provided. It should be noted that, as the dielectric layer mainly composed of a perovskite-type oxide, barium titanate or CSTZ can be preferably employed, and CSTZ can be more preferably employed.
[0116] 3. Paste Coating Process
[0117] In this process, the conductive paste is coated on a part (for example, the side surface) of the surface of the stacked chip prepared above. As the method of coating the conductive paste, for example, dip coating method, dispenser supply method, printing methods such as screen printing, gravure printing, offset printing and inkjet printing, spraying method, etc. can be cited. In the case of forming the external electrode of the MLCC, the dip coating method is more preferable.
[0118] 4. Baking Process
[0119] In this process, the stacked chip coated with the conductive paste is baked at a specified temperature. Thus, an MLCC having a stacked chip and an external electrode is formed. In this process, the conductive particles in the paste are sintered to form a porous baked body, and the glass powder is melted and fills the voids of the baked body. At this time, the glass powder of the conductive paste disclosed herein is configured such that SiO2, Al2O3, B2O3, ZnO, and CaO are set at a specified ratio and substantially do not contain BaO. Thereby, the glass component can be appropriately diffused throughout the external electrode to form an external electrode having sufficient adhesion. It should be noted that the baking temperature (the maximum baking temperature) in this process is preferably 650 °C to 850 °C, and more preferably about 670 °C to 800 °C.
[0120] As described above, as specific embodiments of the technology disclosed herein, the embodiments described in the following items can be cited.
[0121] [Item 1]
[0122] A glass powder for a conductive paste, the glass powder containing the following composition in terms of mass ratio in terms of oxide conversion:
[0123] SiO2: 6 wt% to 18 wt%;
[0124] B2O3: 18 wt% to 30 wt%;
[0125] ZnO: 26 wt% to 47 wt%;
[0126] Al2O3: 2 wt% to 17 wt%;
[0127] CaO: 10 wt% to 25 wt%, and substantially free of BaO.
[0128] [Item 2]
[0129] The glass powder according to Item 1, wherein the glass powder is substantially free of alkaline earth metal oxides other than CaO.
[0130] [Item 3]
[0131] The glass powder according to Item 1 or 2, wherein the softening point of the glass powder is 500 °C or higher and 650 °C or lower.
[0132] [Item 4]
[0133] The glass powder according to any one of Items 1 to 3, wherein the median particle size D 50 of the glass powder is 1 μm or more and 3 μm or less.
[0134] [Item 5]
[0135] The glass powder according to any one of Items 1 to 4, wherein the glass powder contains 20 wt% or more of B2O3 in terms of mass ratio in terms of oxide conversion.
[0136] [Item 6]
[0137] The glass powder according to any one of Items 1 to 5, wherein the glass powder contains 10 wt% or more of Al2O3 in terms of mass ratio in terms of oxide conversion.
[0138] [Item 7]
[0139] A conductive paste containing the glass powder according to any one of Items 1 to 6, conductive particles, and a dispersion medium.
[0140] [Item 8]
[0141] The conductive paste according to Item 7, wherein the conductive particles are Cu particles.
[0142] [Item 9]
[0143] The conductive paste according to Item 7 or 8, wherein when the entire conductive paste is set to 100 wt%, the glass powder is contained in an amount of 4 wt% or more and 12 wt% or less.
[0144] [Item 10]
[0145] A method for manufacturing a multilayer ceramic capacitor, comprising:
[0146] A paste preparation step of preparing a conductive paste containing glass powder, conductive particles, and a dispersion medium;
[0147] A stacked chip preparation step of preparing a stacked chip;
[0148] A paste coating step of coating the conductive paste prepared in the paste preparation step on the surface of the stacked chip prepared in the stacked chip preparation step; and
[0149] A firing step of firing the stacked chip coated with the conductive paste, wherein the glass powder contains the following composition in terms of mass ratio in terms of oxide conversion:
[0150] SiO2: 6 wt% to 18 wt%;
[0151] B2O3: 18 wt% to 30 wt%;
[0152] ZnO: 26 wt% to 47 wt%;
[0153] Al2O3: 2 wt% to 17 wt%;
[0154] CaO: 10 wt% to 25 wt%, and substantially does not contain BaO.
[0155] [Item 11]
[0156] The method for manufacturing a multilayer ceramic capacitor according to Item 10, wherein the stacked chip includes a dielectric layer mainly composed of a perovskite-type oxide.
[0157] [Item 12]
[0158] The method for manufacturing a multilayer ceramic capacitor according to Item 11, wherein (CaSr)(TiZr)O3 is included as the perovskite-type oxide.
[0159] [Item 13]
[0160] The manufacturing method of the multilayer ceramic capacitor according to any one of Items 10 to 12, wherein the firing step is performed at a firing temperature of 650°C or higher and 850°C or lower.
[0161] [Test Example]
[0162] Next, test examples related to the technology disclosed herein will be described. It should be noted that the test examples shown below are not intended to limit the technology disclosed herein.
[0163] [Preparation of Glass Powder]
[0164] (1) Samples 1 to 12
[0165] Here, glass powder (median particle size D 50 : 1.5 μm) for use in the evaluation described later is prepared. It should be noted that the compositions of the glass powders of Samples 1 to 12 are shown in Table 1.
[0166] [Evaluation of Glass Powder]
[0167] 1-1. Evaluation of Adhesion Strength
[0168] In this test, the adhesion strength of the glass powders of the respective samples prepared above is evaluated.
[0169] (1) Preparation of Test Pieces
[0170] First, as conductive particles, plate-shaped Cu particles (median particle size D 50 : 4 μm) are prepared. For the above Cu particles, the glass powders of each example are mixed at an external addition ratio of 11 wt%. Then, by press molding, button-shaped pellets of φ15 mm × 1.5 mm are produced. Next, a mixture of CSTZ powder and a binder (aqueous polyvinyl alcohol solution) is press molded and fired at 1280°C for 2 hours in an air atmosphere. Thus, a flat plate-shaped substrate (hereinafter referred to as CSTZ substrate) having dimensions of 26 mm × 26 mm × 1.3 mm is prepared. Then, the above-obtained pellets are placed on the prepared CSTZ substrate, and a firing treatment is performed at 730°C for 30 minutes in a nitrogen atmosphere. Thus, test pieces obtained by firing the pellets on the substrate are obtained.
[0171] (2) Adhesion Strength Test
[0172] Using a 4000 universal bonding tester manufactured by Nordson DAGE, a load was applied to the pellets at room temperature, and the strength (bonding strength) at the time of pellet peeling was measured. Specifically, the substrate portion of the test piece prepared as described above was fixed to the testing machine, and a shearing force was applied to the pellets in a direction horizontal to the bonding surface using a shearing tool. Then, the strength at the time of peeling the pellets from the substrate was taken as the bonding strength (N).
[0173] This evaluation was performed on each sample with N = 3, and the arithmetic mean value (Ave. value) of the bonding strength was calculated. Then, for each sample, the case where the Ave. value exceeded 20 N was regarded as qualified. The results are shown in Table 1. It should be noted that the larger the value of the bonding strength, the better the bonding performance of the pellets (i.e., the glass powder) (i.e., the less likely to peel off).
[0174] [Table 1]
[0175]
[0176] As shown in Table 1, in Samples 5 to 7 in which BaO is contained in the glass powder, sufficient bonding performance could not be obtained for the CSTZ substrate. On the other hand, in Samples 1 to 4, sufficient bonding strength could be confirmed. From this, it can be seen that when the glass powder for the conductive paste is the glass powder of the composition of the present disclosure as in Samples 1 to 4, sufficient bonding strength is obtained for the CSTZ substrate. On the other hand, for the pellets obtained from the conductive paste of Samples 8 to 12, the bonding strength was not obtained either. It is considered that this is because the composition of the glass powder used in the conductive paste of Samples 8 to 12 is outside the scope of the present disclosure.
[0177] 2-1. Study on Bonding Strength Based on Difference in Firing Temperature
[0178] In order to further evaluate the bonding performance of the glass powder of the present disclosure, in this experiment, a study on the bonding strength at different firing temperatures was conducted on the evaluation pastes of Sample 1 and Sample 2. Specifically, first, pellets of Sample 1 and a CSTZ substrate were prepared by the same method as described above. Then, the firing treatment temperature was set to 710 °C, and except for this, a test piece having a fired film formed on the CSTZ substrate was obtained in the same manner as in 1-1. above. For this test piece, a bonding strength test was performed in the same manner as the above method. In addition, for Sample 2, pellets and a CSTZ substrate were also prepared under the same conditions, and a bonding strength test was performed under the same conditions as Sample 1. The results are shown in Table 2.
[0179] [Table 2]
[0180] Table 2
[0181]
[0182] As shown in Table 2, for Sample 1, even when the pellets were calcined at 710 °C, good bonding strength could be confirmed. Additionally, for Sample 2 as well, good bonding strength was obtained when calcined at 710 °C.
[0183] 2-2. Study on the Bonding Strength of Barium Titanate Substrate (BT Substrate)
[0184] In this experiment, the bonding strength of the glass powder of Sample 1 and Sample 2 to the BT substrate was studied. Specifically, first, the pellets of Sample 1 were prepared using the same method as above. Then, a mixture of barium titanate powder and binder was compression-molded and calcined at 1300 °C for 2 hours in an air atmosphere. Thus, a flat-plate-shaped barium titanate substrate (hereinafter referred to as BT substrate) with dimensions of 26 mm × 26 mm × 1.3 mm was prepared. Then, the pellets of Sample 1 were placed on the above BT substrate, and a calcination treatment was carried out for 30 minutes in a nitrogen atmosphere. Thus, test pieces were obtained. It should be noted that in order to evaluate the bonding strength at each calcination temperature, test pieces calcined at 730 °C or 710 °C were respectively fabricated. For these test pieces, the bonding strength test was carried out in the same manner as the above method. Additionally, for Sample 2, pellets and BT substrates were prepared under the same conditions, and the bonding strength test was carried out under the same conditions as Sample 1. The results are shown in Table 3.
[0185] [Table 3]
[0186] Table 3
[0187]
[0188] As shown in Table 3, it could be confirmed that when the bonding strength test was carried out using the BT substrate instead of the CSTZ substrate, both Sample 1 and Sample 2 could obtain good bonding strength. From the perspective of the calcination temperature, it could be confirmed that good bonding strength could also be obtained when the BT substrate was calcined at 710 °C.
[0189] 3. Scratch Evaluation
[0190] Here, in order to further evaluate the properties of the glass powder of the present disclosure, the glass powder of Sample 1, Samples 4 - 5, and 12 was evaluated using a scratch test.
[0191] (1) Preparation of Conductive Paste for Evaluation
[0192] First, a conductive paste for evaluation was prepared. Specifically, first, a conductive paste was prepared by mixing 74 wt% of conductive particles (median particle size D 50: A conductive paste composed of 4 - μm plate - shaped Cu particles), 8 wt% glass powder of Samples 1, 4 - 5, and 12, 5 wt% binder (acrylic resin, molecular weight 150,000 - 200,000), 12.7 wt% dispersion medium (dihydroterpineol), and 0.3 wt% dispersant (carboxylic acid - based dispersant). Thus, the conductive pastes for evaluation of Samples 1, 4 - 5, and 12 were obtained.
[0193] (2) Formation of evaluation electrodes
[0194] First, a stacked chip (stacked ceramic capacitor green body) obtained by laminating a dielectric layer mainly composed of CSTZ and internal electrodes of 0402 size was prepared. The conductive paste for evaluation of Sample 1 was coated on the part where the internal electrode was exposed on the end face of the stacked chip. It should be noted that the dip - coating method was used for coating the paste. Then, using a hot - air dryer, a drying treatment was carried out at 120 °C for 10 minutes. Then, a firing treatment was performed on the formed dry film. It should be noted that the firing time was set to 10 minutes, and the total treatment time including the heating - up time (the time from the start to the end of firing) was set to 1 hour. The firing atmosphere was set to a nitrogen atmosphere. It should be noted that in this evaluation, in order to study the difference in the scratching strength of the external electrode caused by the firing temperature, for each sample, electrodes with the firing temperature of the dry film changed to 700 °C, 715 °C, 730 °C, and 750 °C respectively were prepared as evaluation electrodes. In this way, the conductive paste for evaluation of Sample 1 was used as an external electrode to form an evaluation electrode on the surface of the stacked chip. In addition, for Samples 4, 5, and 12, the formation of evaluation electrodes was also carried out under the same conditions.
[0195] (3) Scratch test
[0196] For the above - obtained evaluation electrodes, the scratch strength (scraping strength) of the external electrode was evaluated at room - temperature environment. After the test, the state of the external electrode was observed with an optical microscope. Figure 2 is a photograph after the scratch test of the evaluation electrode formed using Sample 1. Figure 3 is a photograph after the scratch test of the evaluation electrode formed using Sample 4. Figure 4 is a photograph after the scratch test of the evaluation electrode formed using Sample 5. Figure 5 is a photograph after the scratch test of the evaluation electrode formed using Sample 12. It should be noted that Figures 2 to 5 the bright part in the upper half of [[ ]] represents the external electrode formed on the substrate, and the dark part represents the peeling (damage) of the external electrode from the substrate.
[0197] As Figure 4 and Figure 5As shown, in the external electrodes obtained by baking Sample 5 and Sample 12, peeling of the external electrodes after the scratch test was significantly observed. On the other hand, as Figure 2 and Figure 3 shown, in the external electrodes of Sample 1 and Sample 4, when baked at any of the baking temperatures, suppression of peeling of the external electrodes was confirmed as compared with Sample 5 and Sample 12. From this, it can be seen that the external electrodes of Sample 1 and Sample 4 have good scratch strength with respect to the stacked chip (stacked ceramic capacitor green body).
[0198] As described above, the technology disclosed herein has been described in detail, but these are merely examples, and various modifications can be made to the present disclosure without departing from its gist.
Claims
1. A glass powder for a conductive paste, wherein the glass powder comprises the following composition in terms of mass ratio of oxides: SiO2: 6wt%~18wt%; B2O3: 18wt%~30wt%; ZnO: 26wt%~47wt%; Al2O3: 2wt%~17wt%; CaO: 10wt%~25wt%, Furthermore, BaO is substantially not contained.
2. The glass powder according to claim 1, wherein The glass powder does not substantially contain alkaline earth metal oxides other than CaO.
3. The glass powder according to claim 1 or 2, wherein The glass powder has a softening point of 500° C. or higher and 650° C. or lower.
4. The glass powder according to claim 1 or 2, wherein The median particle size D of the glass powder 50 It is not less than 1 μm and not more than 3 μm.
5. The glass powder according to claim 1 or 2, wherein The glass powder contains 20 wt % or more of B 2 O 3 in terms of mass ratio of oxide.
6. The glass powder according to claim 5, wherein The glass powder contains 10 wt % or more of Al 2 O 3 in terms of mass ratio of oxide. 7 . A conductive paste comprising the glass powder according to claim 1 , conductive particles, and a dispersion medium.
8. The conductive paste according to claim 7, wherein The conductive particles are Cu particles.
9. The conductive paste according to claim 7, wherein The conductive paste contains the glass powder in an amount of 4 wt % to 12 wt % inclusive, based on 100 wt % of the entire conductive paste.
10. A method for manufacturing a laminated ceramic capacitor, comprising: a paste preparation step of preparing a conductive paste comprising glass powder, conductive particles and a dispersion medium; A stacked chip preparation process, preparing stacked chips; a paste coating step of coating the conductive paste prepared in the paste preparation step on the surface of the stacked chip prepared in the stacked chip preparation step; and a baking step of baking the laminated chip coated with the conductive paste, The glass powder comprises the following composition in terms of mass ratio of oxides: SiO2: 6wt%~18wt%; B2O3: 18wt%~30wt%; ZnO: 26wt%~47wt%; Al2O3: 2wt%~17wt%; CaO: 10wt%~25wt%, Furthermore, BaO is substantially not contained.
11. The method for manufacturing a multilayer ceramic capacitor according to claim 10, wherein: The stacked chip includes a dielectric layer containing a perovskite-type oxide as a main component.
12. The method for manufacturing a multilayer ceramic capacitor according to claim 11, wherein: The perovskite type oxide includes (CaSr)(TiZr)O3.
13. The method for manufacturing a multilayer ceramic capacitor according to claim 10 or 11, wherein: The calcination step is performed at a calcination temperature of 650° C. to 850° C. both inclusive.
Citation Information
Patent Citations
Disc recording / Reproducing apparatus
JP1996017140A
Cited By
Preparation method and application of oxide glass electrode of lithium ion capacitor
CN121964397A
A method for the preparation of lithium-ion capacitor oxide glass electrodes and uses thereof
CN121964397B